Anti-adipogenic and anti-obesity activities of purpurin in 3T3-L1 preadipocyte cells and in mice fed a high-fat diet - Woo Nam; Seok Hyun Nam; Sung Phil Kim; Carol Levin; Mendel Friedman (BMC, 2019)
Abstract Background The body responds to overnutrition by converting stem cells to adipocytes. In vitro and in vivo studies have shown polyphenols and other natural compounds to be anti-adipogenic, presumably due in part to their antioxidant properties. Purpurin is a highly antioxidative anthraquinone and previous studies on anthraquinones have reported numerous biological activities in cells and animals. Anthraquinones have also been used to stimulate osteoblast differentiation, an inversely-related process to that of adipocyte differentiation. We propose that due to its high antioxidative properties, purpurin administration might attenuate adipogenesis in cells and in mice. Methods Our study will test the effect purpurin has on adipogenesis using both in vitro and in vivo models. The in vitro model consists of tracking with various biomarkers, the differentiation of pre-adipocyte to adipocytes in cell culture. The compound will then be tested in mice fed a high-fat diet. Murine 3T3-L1 preadipocyte cells were stimulated to differentiate in the presence or absence of purpurin. The following cellular parameters were measured: intracellular reactive oxygen species (ROS), membrane potential of the mitochondria, ATP production, activation of AMPK (adenosine 5'-monophosphate-activated protein kinase), insulin-induced lipid accumulation, triglyceride accumulation, and expression of PPARγ (peroxisome proliferator activated receptor-γ) and C/EBPα (CCAAT enhancer binding protein α). In vivo, mice were fed high fat diets supplemented with various levels of purpurin. Data collected from the animals included anthropometric data, glucose tolerance test results, and postmortem plasma glucose, lipid levels, and organ examinations. Results The administration of purpurin at 50 and 100 μM in 3T3-L1 cells, and at 40 and 80 mg/kg in mice proved to be a sensitive range: the lower concentrations affected several measured parameters, whereas at the higher doses purpurin consistently mitigated biomarkers associated with adipogenesis, and weight gain in mice. Purpurin appears to be an effective antiadipogenic compound. Conclusion The anthraquinone purpurin has potent in vitro anti-adipogenic effects in cells and in vivo anti-obesity effects in mice consuming a high-fat diet. Differentiation of 3T3-L1 cells was dose-dependently inhibited by purpurin, apparently by AMPK activation. Mice on a high-fat diet experienced a dose-dependent reduction in induced weight gain of up to 55%.